Comparative Transcriptome Reconstruction of Four Hypericum Species Focused on Hypericin Biosynthesis - Soták, Miroslav; Czeranková, Odeta; Klein, Daniel; Jurčacková, Zuzana; Li, Ling; Čellárová, Eva (Frontiers in Plant Science, 2016)
Next generation sequencing technology (NGS) rapidly developed research applications in the field of plant functional genomics. Several Hypericum spp. with an aim to generate and enhance gene annotations especially for genes coding the enzymes supposedly included in biosynthesis of valuable bioactive compounds were analyzed. The first de novo transcriptome profiling of H. annulatum Moris, H. tomentosum L., H. kalmianum L. and H. androsaemum L. leaves cultivated in vitro was accomplished. All four species with only limited genomic information were selected on the basis of differences in ability to synthesize hypericins and presence of dark nodules accumulating these metabolites with purpose to enrich genomic background of Hypericum spp. H. annulatum was chosen because of high number of the dark nodules and high content of hypericin. H. tomentosum leaves are typical for the presence of only 1-2 dark nodules localized in the apical part. Both H. kalmianum and H. androsaemum lack hypericin and have no dark nodules. Four separated datasets of the pair-end reads were gathered and used for de novo assembly by Trinity program. Assembled transcriptomes were annotated to the public databases Swiss-Prot and non-redundant protein database (NCBI-nr). Gene ontology analysis was performed. Differences of expression levels in the marginal tissues with dark nodules and inner part of leaves lacking these nodules indicate a potential genetic background for hypericin formation as the presumed site of hypericin biosynthesis is in the cells adjacent to these structures. Altogether 165 contigs in H. annulatum and 100 contigs in H. tomentosum were detected as significantly differentially expressed (P<0.05) and upregulated in the leaf rim tissues containing the dark nodules. The new sequences homologous to octaketide synthase and enzymes catalyzing phenolic oxidative coupling reactions indispensable for hypericin biosynthesis were discovered. The presented transcriptomic sequence data will improve current knowledge about the selected Hypericum spp. with proposed relation to hypericin biosynthesis and will provide a useful resource of genomic information for consequential studies in the field of functional genomics, proteomics and metabolomics.